Aktivitas Belajar Siswa Melalui Metode Pembelajaran Inkuiri Pada Mata Pelajaran Pendidikan Agama Islam - Mutho'i, Mutho'i; Dwistia , Halen (LP3M STAI Ibnurusyd, 2023)
Student activities are students' activities to build their knowledge by actively asking questions,expressing ideas, solving problems and doing direct activities. The inquiry learning method is a studentcenteredstrategy where groups of inquiry students seek answers to the contents of statementsthrough clearly outlined procedures and group structure. The researcher concluded that applying theinquiry method can provide students with the opportunity to be actively involved in problem solvingthrough systematic steps. Apart from that, the guided inquiry method will make students have theskills to work and think regularly and systematically. Especially for Islamic religious education lessons,with this method students will be required to search for various material systematically and indirectlyit will be easier for students to remember all the material about Islamic knowledge that they arelooking for.